Microbial insights into ruminal fiber degradation and feed efficiency of Hu sheep - Xu, Haoyu; Wang, Guoxiu; Gao, Qihao; Liu, Zhen; Jia, Jiale; Xu, Yunfei; Chen, Zhanyu; Li, Baosheng; Li, Chong (Frontiers in Microbiology, 2025)
Ruminal fiber degradation is essential for feed conversion efficiency in sheep; however, it remains unclear whether individual variations in ruminal fiber degradation directly affect feed conversion efficiency. Here, the relationship between ruminal fiber degradation rate and feed conversion efficiency and influence of rumen structure, function, and microbiota on fiber degradation were investigated. A total of 190 male Hu lambs were randomly selected, raised from birth to 180 days, and slaughtered. The relationships between ruminal fiber degradation rate and feed conversion efficiency, growth performance, and ruminal fermentation parameters were analyzed. Key microorganisms influencing ruminal fiber degradation were identified using multiple methods: microbial wide association study, correlation analysis, and differential abundance analysis. Both neutral detergent fiber (NDF) and acid detergent fiber (ADF) degradation rates were significantly correlated with feed conversion efficiency and intake. Seven genera were closely associated with NDF degradation rate: 6 belonged to Firmicutes (Anaerotruncus, Family_XIII_UCG-002, Lachnoclostridium_1, Moryella, Ruminococcaceae_NK4A214_group, and Veillonellaceae_UCG-001); 1, Bacteroidetes (Prevotellaceae_UCG-003). Eight genera were closely associated with ADF degradation rate: 6, Firmicutes (Lachnospiraceae_ND3007_group, Family_XIII_UCG-002, Lachnoclostridium_1, Lachnospiraceae_UCG-002, Moryella, and Ruminococcaceae_NK4A214_group); 1, Bacteroidetes (Prevotellaceae_UCG-003); and 1, Actinobacteria (Olsenella). In conclusion, high ruminal fiber degradation rates significantly enhance feed conversion efficiency, with specific microbial genera from the phylum Firmicutes and family Lachnospiraceae playing pivotal roles in fiber utilization. These findings provide a microbial basis for optimizing rumen fiber degradation efficiency in sheep and highlight the potential of uncultured taxa as future targets for improving feed conversion efficiency.